Research on Microstructure and Mechanical Properties of Ultrasonic-Assisted Gas Metal Arc Welding Additive Manufacturing with High-Nitrogen Steel Welding Wire - Jiawen Luo; Zhizheng He; Zihuan Hua; Chenglei Fan (Metals)
High-nitrogen steels (HNSs) are valued for their superior mechanical strength and corrosion resistance, making them ideal for high-end industrial applications. However, nitrogen loss during gas metal arc welding additive manufacturing (GMAW-AM) often results in porosity and coarse microstructures, degrading component performance. This study introduces a coaxial ultrasonic-assisted GMAW-AM (U-GMAW-AM) process to mitigate nitrogen loss and refine the microstructure. Welding wires with 0.35 wt.% and 0.70 wt.% nitrogen were used to examine the effects of welding voltage (24.5–30 V) and ultrasonic power (0–2 kW). The results show that a higher voltage increases nitrogen evaporation, with a maximum loss of 0.22% at 30 V. In contrast, ultrasonic assistance reduces nitrogen loss by up to 29.17% for the 0.70 wt.% wire. Microstructural analysis reveals a significant reduction in ferrite and enhanced austenite formation due to better nitrogen retention. Mechanical testing shows that ultrasonic assistance improves tensile strength by 100 MPa (up to 919.1 MPa), elongation by nearly 10%, and hardness uniformity. These findings highlight the potential of ultrasonic assistance for optimizing high-nitrogen steel properties in additive manufacturing.